A Study on the Use Intention of Long Term Evolution Mobile Service - Lee, Joo Yeoun; Kang, Tae Gu (Wireless Personal Communications, 2018)
The rapid development of ICT is bringing about a digital transformation. The digital transformation affects all areas, and ICT is at the center of many technologies. In particular, the importance of technical services for wireless communications is being increasingly emphasized. Thus, the qualities of technical services for wireless communications have effects not only on the companies who provide services but also on the consumers who receive them. As technologies develop, consumers want to receive more stable and higher quality services. In this regard, this study classified the qualities of LTE service into call quality, speed quality, and user support quality, investigated their influential factors on perceived usefulness, perceived ease of use, and playfulness, and analyzed their causal relationship with satisfaction and continuous use intention. As a result of analysis, all the hypotheses were accepted; except for the one that call quality will have effects on perceived usefulness (H1-1), except for the one that social influence will have effects on user satisfaction (H7-2), except for the one that customer membership will have effects on perceived usefulness (H8-1), except for the one that social influence will have effects on perceived usefulness (H8-2). The results of this study provided practical guidelines to service providers through the causal relationship analysis of various variables affecting LTE services satisfaction and constant services.
Keywords: Digital transformation; Perceived ease of use; Playfulness; Practical guidelines; Satisfaction; Service Quality; Use intentions; Wireless communications; Continuous use intention; LTE; Playfulness; PLS; Satisfaction; Service quality